Green in blue: The environmental impacts of jazz production and consumption - Medbøe, Haftor (Jazz Research Journal, 2024)
The global commodification of jazz (and indeed culture more generally) has contributed to significant and enduring environmental consequences. The various physical formats through which it has been disseminated have each employed by-products of the petrochemical industry in their production and distribution, and the environmental cost of digital streaming platforms has more recently been observed as contributing further to the carbon footprints of music producers and consumers. International and regional travel by touring artists and festival audiences has similarly been recognized as having negative environmental impacts through associated air, sea, and land transport emissions and through increased burden on host-location infrastructures. The environmental implications of culture have come increasingly under scrutiny as society becomes conscious of individual and collective contributions to, and imperative mitigations against, critical anthropogenic climate change. This article seeks to explore the machineries of jazz dissemination, foregrounding the festival as a place of coming together in celebration of music and community, and considers how the road ahead may look as we attempt to green our engagement with culture while safeguarding its intrinsic values and modes of experience. It questions, therefore, whether the art form that spearheaded the ways in which we currently interact with live and recorded music can similarly lead us in addressing urgent and necessary paradigm shifts in the means and methods of cultural production and consumption.